Biologically active natural products : Agrochemicals - Cutler, Horace G; Ed. Cutler, Stephen J; Ed (CRC PRESS, 1999)
Natural products that have both plant growth regulatory and pharmaceutical properties are examined in this book. This is the first and most up-to-date text linking agrochemistry and pharmaceutical chemistry in an easy-to-read presentation for practitioners in both fields. Featuring over 200 tables, Biologically Active Natural Products: Agrochemicals is very useful to those in the agrochemical and pharmaceutical industries, as well as those in biochemistry, plant pathology, and natural products study and development.